Gerakan Tangan Pemain Otomatis Menggunakan Computer Vision - Fahrudin, Fikri; Andriani, Mesi; Muallimin; Altiarika, Eka (Universitas Muhammadiyah Bangka Belitung, 2023)
Gesture recognition allows users of computer science technology to connect with their digital devices more conveniently. Technology for gesture recognition can be helpful in a variety of contexts, such as automated household appliances, automobiles, and interpretation of hand gestures. Gesture recognition is part of gesture recognition which determines what message a certain hand movement wants to convey. In developing this automatic hand movement we use segmentation and object detection where this method involves using algorithms to detect and identify objects or areas related to hand movements. , such as human skin, fingers, and others. Detection of human hand movements using computer vision is a digital image processing technique that aims to recognize human hand movements from image or video data. This technique can be applied in various applications such as human-computer interaction, hand gesture recognition, or video games. Making Automatic Player Hand Movements Using Computer Vision has the potential to improve the user experience when playing games or using interactive applications that require hand movements, according to the research and development that has been done. Games could be controlled more precisely and with less need for additional hardware such as joysticks or controllers if computer vision technology was able to accurately distinguish hand movements.